2023
DOI: 10.1186/s12889-023-15383-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with severity and anatomical distribution of diabetic foot ulcer in Uganda: a multicenter cross-sectional study

Abstract: Background Diabetic foot ulcer (DFU) is a devastating complication of diabetes mellitus (DM) that is associated with increased mortality, morbidity, amputation rate and economic burden. This study aimed at identifying the anatomical distribution and factors associated with severity of DFU in Uganda. Methodology This was a multicenter cross-sectional study conducted in seven selected referral hospitals in Uganda. A total of 117 patients with DFU wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…A body of research has underscored the adverse consequences associated with delayed diagnosis, including an elevated risk of infection, amputation, and mortality. [4][5][6][7][32][33][34] Within LMICs, investigations have consistently demonstrated that early identification of DFUs confers numerous advantages, encompassing higher healing rates, reduced amputation frequencies, decreased health care expenditures, and enhanced overall quality of life for affected individuals. [4][5][6][7] The contrast in mortality rates between LMICs and HICs further underscores the significance of early identification.…”
Section: Early Identification and Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…A body of research has underscored the adverse consequences associated with delayed diagnosis, including an elevated risk of infection, amputation, and mortality. [4][5][6][7][32][33][34] Within LMICs, investigations have consistently demonstrated that early identification of DFUs confers numerous advantages, encompassing higher healing rates, reduced amputation frequencies, decreased health care expenditures, and enhanced overall quality of life for affected individuals. [4][5][6][7] The contrast in mortality rates between LMICs and HICs further underscores the significance of early identification.…”
Section: Early Identification and Diagnosismentioning
confidence: 99%
“… 4 , 5 , 6 , 7 , 32 , 33 , 34 Within LMICs, investigations have consistently demonstrated that early identification of DFUs confers numerous advantages, encompassing higher healing rates, reduced amputation frequencies, decreased health care expenditures, and enhanced overall quality of life for affected individuals. 4 , 5 , 6 , 7 …”
Section: Importance Of Early Intervention and Adequate Care Of Dfu; E...mentioning
confidence: 99%
See 2 more Smart Citations
“…Surveys with small sizes have, for example, revealed that diabetes is one of the leading causes of blindness, kidney failure, heart attack, stroke and non-traumatic lower limb amputation in Uganda. 16 In addition, 27% of the diabetics are obese, 36% are overweight 17 and 4% have diabetic foot, 18 yet majority are not aware that they may develop reduced blood flow in their feet caused by smoking. 19 …”
Section: Introductionmentioning
confidence: 99%